Economic burden of measles and its influencing factors in Fujian, China. Issue 12 (2nd December 2021) - Chen, Junlei; Jia, Haimei; Cai, Zhikun; Zhou, Yong; Ma, Shanshan; Chen, Yahong; Chen, Changfu; Pan, Weiyi
ABSTRACT: Background: Measles is a highly-contagious, serious diseases that can lead to potentially fatal illness, disability and death . We conducted an investigation to calculate the economic burden of measles cases from 2018 to 2019 and to analyze factors that influenced the total costs of measles cases in Fujian Province, China. Methods: We investigated confirmed cases of measles by telephone interview, from 2018 to 2019, including demographic characteristics, therapeutic measures, self-treatment and nutritional supplement expenditure, transportation fees, and lost wages. Medical expenses in the hospitals were obtained from the hospital service charge system. Results: A total of 131 measles cases were investigated, the average direct cost, indirect cost, and total cost were $518, $284, and $802, respectively. The total cost was 15.5% of Annual Per Capita Disposable Income of Households ($5 162) in Fujian. Hospitalization ( OR  = 98.6, 95% CI : 21.1 ~ 460.6) and complication ( OR  = 8.7, 95% CI : 1.3 ~ 58.0) significantly influenced the total cost according to binary logistic regression, and an outbreak of measles may pose a significant threat to household finances in a short term. Conclusions: The economic burden of measles was high when compared with Annual Per Capita Disposable Income of Households. The resurgence of measles and measles outbreaks increased economic burden of household finances.